KONSTRUKSI VERBA GERAK DIREKSIONAL DALAM BAHASA BANJAR - Ahmad Imam Muttaqin (PRASASTI: Journal of Linguistics, 2019)
Directional motion verbs construction classify a language into two types: satellite-framed language and verb-framed language. Based on two components: ‘path’ that contained directional meaning, and ‘manner of motion’ that contained the way verbs/something done. The concept of language typology related with directional motion verbs construction pioneered by Talmy (1985) is to put it universally, and actually it does work when it faced with Banjarese which is the main language of South Borneo. There is no one ever researched about directional motion verbs in Banjarese before, so it is important to make one and hopefully it would trigger another interest from people to research Banjarese. This paper aims to discuss directional motion verbs in Banjarese, to classify the frame of Banjarese, and also to evaluate whether Talmy’s typology is relevant for Banjarese. The results of the analysis show that directional verbs in Banjarese are using preposition, so Banjarese can be said as a satellite-framed language. The adjectival resultatives that also one of the character of satellite-framed language according to Talmy’s statement also can be found in Banjarese.Key Words: Directional motion verbs, Language typology, Banjarese